Learning Strategies at SMA Muhammadiyah 4 Porong During Covid-19 Pandemic - Muhlasin Amrullah; Masfufah Hanim (International Consortium of Education and Culture Research Studies, 2021)
The current Covid-19 pandemic has had a very broad impact on the joints of life, including in the field of education. So that the government implements a Distance Learning policy or online. This is to break the chain of the spread of the corona virus in schools and universities. This change in the education system makes it difficult for students to accept and understand the material presented, because learning which is usually carried out in person or face-to-face has turned into Distance Learning or is carried out online, whose implementation cannot be separated by utilizing information technology. This study aims to describe the Learning Strategy of SMA Muhammadiyah 4 Porong in the Middle of the Covid-19 Pandemic. This research was conducted on high school students in Sidoarjo Regency. In the research process this time using descriptive qualitative research methods. The learning strategy applied by SMA Muhammadiyah 4 Porong during the pandemic was to use 2 learning methods, namely online learning methods and offline learning methods. The online learning method is done by communicating via WhatsApp, the teacher provides material or assignments via WhatsApp messages in the form of text, video, and powerpoint. And still comply with the health protocol for students who take offline or offline learning. However, this kind of learning technique is important to evaluate, considering the ability of parents to provide online learning facilities. Technology has a very big role to facilitate educators in delivering learning materials so that learning can continue even though it cannot be done face-to-face. In the implementation of online learning, there are obstacles that are a challenge for educators, related to academics, as well as the readiness of facilities and infrastructure related to technology.